Vanajyotsnā-sahastrasaumanasī = Vanajyotsnā-sahasrasaumanasī : Flora & plant kingdom in Sanskrit literature - Chatterjee, Jyotsnamoy, 1927-2001.; Kulashreshtha, Abha, 1952-; Kulaśreshṭha, Jagadīśa Sahāya, 1922-; Kulaśreshṭha, Sushamā, 1945-; Anju Bālā. (Delhi : Eastern Book Linkers, 2003)
Contributed articles on flora and fauna in Sanskrit literature; festschrift in honor of 75th birth anniversary of Jyotsnamoy Chatterjee, 1927-2001.
"Jyotsnamoy Chatterjee festschrift."
Sadrži bibliografske bilješke.
Sanskrt, engleski i hindski.
Keywords: indijska klasična književnost -- sanskrtska književnost - teorija i kritika -- flora u književnosti; indijska kultura i civilizacija